The Supreme Court and the Fourth Amendment's exclusionary rule - Maclin, Tracey (Oxford ; New York : Oxford University Press, 2013)
The application of the Fourth Amendment's exclusionary rule has divided the justices of the Supreme Court for nearly a century. This book traces the rise and fall of the exclusionary rule with insight and behind-the-scenes access into the Court's thinking.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United States; United States. -- Supreme Court; Exclusionary rule (Evidence) -- United States; Searches and seizures -- United States